Cytotaxonomy, morphology and ecology of the Simulium nobile species group (Diptera: Simuliidae) in Thailand - U. Tangkawanit (2018)
The polytene chromosomes of 512 larvae of the Simulium nobile species group collected from 16 stream sites in northern, central and southern Thailand were examined. Band-by- band comparisons relative to the established standard chromosome map for the subgenus Simulium distinguished the 2 species of this group, S. nobile and S. nodosum. The differences are mainly due to the position of the nucleolar organizer, pseudochromocenter, and fixed and polymorphic inversions. S. nobile is a monomorphic species, while S. nodosum is a polymorphic species. The morphology of these taxa is described based on the gill filaments and the color of the antennae and female genitalia. S. nobile is distributed in southern Thailand at low altitudes, whereas the distribution of S. nodosum is in the north at higher altitudes. Copyright © 2011 S. Karger AG, Basel.